Polyunsaturated fatty acids in relation to incident mobility disability and decline in gait speed; the Age, Gene/Environment Susceptibility-Reykjavik Study - Reinders, I; Murphy, R A; Song, X; Visser, M; Cotch, M F; Lang, T F; Garcia, M E; Launer, L J; Siggeirsdottir, K; Eiriksdottir, G; Jonsson, P V; Gudnason, V; et al. (European journal of clinical nutrition, 2015)
Background/Objectives: Low intake of long chain polyunsaturated fatty acids (PUFAs) are associated with physical disability; however, prospective studies of circulating PUFAs are scarce. We examined associations between plasma phospholipid n −3 and n −6 PUFAs with risk of incident mobility disability and gait speed decline. Subjects/Methods: Data are from a subgroup of the Age, Gene/Environment Susceptibility–Reykjavik Study, a population-based study of risk factors for disease and disability in old age. In this subgroup ( n =556, mean age 75.1±5.0 years, 47.5% men), plasma phospholipid PUFAs were assessed at baseline using gas chromatography. Mobility disability and usual gait speed were assessed at baseline and after 5.2±0.2 years. Mobility disability was defined as the following: having much difficulty, or being unable to walk 500 m or climb up 10 steps; decline in gait speed was defined as change ⩾0.10 m/s. Logistic regression analyses were performed to determine associations between sex-specific s.d. increments in PUFAs with risk of incident mobility disability and gait speed decline. Odds ratios (95% confidence intervals) adjusted for demographics, follow-up time, risk factors and serum vitamin D were reported. Results: In women, but not men, every s.d. increment increase of total n −3 PUFAs and docosahexaenoic acid (DHA) was associated with lower mobility disability risk, odds ratio 0.48 (0.25; 0.93) and odds ratio 0.45 (0.24; 0.83), respectively. There was no association between n −6 PUFAs and the risk of incident mobility disability or gait speed decline. Conclusions: Higher concentrations of n −3 PUFAs and, particularly, DHA may protect women from impaired mobility but does not appear to have such an effect in men.